2022
DOI: 10.1002/cne.25344
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal development of the human entorhinal cortex

Abstract: Little is known about the development of the human entorhinal cortex (EC), a major hub in a widespread network for learning and memory, spatial navigation, high‐order processing of object information, multimodal integration, attention and awareness, emotion, motivation, and perception of time. We analyzed a series of 20 fetal and two adult human brains using Nissl stain, acetylcholinesterase (AChE) histochemistry, and immunocytochemistry for myelin basic protein (MBP), neuronal nuclei antigen (NeuN), a pan‐axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 199 publications
2
8
0
Order By: Relevance
“…While in the isocortical cingulate cortex SP expansion-deep CP cells "spread down" (Duque et al 2016) precedes by neocortical mode, the ventral primordial cingulate belt shows incomplete CP "delamination" and SP is extremely narrow at the border with a curved thin cortical sheet of the supracallosal archicortex-future indusium griseum ("dorsal hippocampus"). This new finding via DPN markers confirms histological observation of Kostović and Krmpotić (1976), synaptic distribution analysis in the interhemispheric cortex (Kostović and Krmpotić-Nemanić 1975;Kostović et al 2004), structural MRI (Bobić-Rasonja et al 2021, as well as the concept of the thin SP and MZ enlargement as a characteristic of the limbic allocortex (Kostović et al 1989;Supèr et al 1998;Šimić et al 2022). Using the atypical SP formation process in the ventral cingulate cortex, our study demonstrated that before the cingulate sulcus and callosal sulcus formation, mesocortex occupied a large portion of the interhemispheric cortical mantle (His 1904;Hochstetter 1919;Economo and Koskinas 1925), nicely summarized in Figure 121 by Stephan (1975).…”
Section: Subplate Formation (Expansion) Phase Is a Hallmark Of The Hu...supporting
confidence: 80%
“…While in the isocortical cingulate cortex SP expansion-deep CP cells "spread down" (Duque et al 2016) precedes by neocortical mode, the ventral primordial cingulate belt shows incomplete CP "delamination" and SP is extremely narrow at the border with a curved thin cortical sheet of the supracallosal archicortex-future indusium griseum ("dorsal hippocampus"). This new finding via DPN markers confirms histological observation of Kostović and Krmpotić (1976), synaptic distribution analysis in the interhemispheric cortex (Kostović and Krmpotić-Nemanić 1975;Kostović et al 2004), structural MRI (Bobić-Rasonja et al 2021, as well as the concept of the thin SP and MZ enlargement as a characteristic of the limbic allocortex (Kostović et al 1989;Supèr et al 1998;Šimić et al 2022). Using the atypical SP formation process in the ventral cingulate cortex, our study demonstrated that before the cingulate sulcus and callosal sulcus formation, mesocortex occupied a large portion of the interhemispheric cortical mantle (His 1904;Hochstetter 1919;Economo and Koskinas 1925), nicely summarized in Figure 121 by Stephan (1975).…”
Section: Subplate Formation (Expansion) Phase Is a Hallmark Of The Hu...supporting
confidence: 80%
“…Along with the maturation of excitatory neurons of the network, maturation-related increase in PV expression across the entire entorhinal-hippocampal complex is influenced by the activity of stellate cells in layer 2 of the medial entorhinal cortex (Donato et al, 2017 ). The coincidence of the postnatal development of PV-immunoreactive neurons found in the human entorhinal cortex by Grateron et al ( 2003 ) and the prolonged maturation of these cells found by us in the Ammon’s horn and the dentate gyrus, along with other developmental studies indicates the relevancy of the coupled and sequential maturation of the entorhinal-hippocampal network (Liu et al, 2021 ; Šimić et al, 2022 ).…”
Section: Discussionmentioning
confidence: 51%
“…The development of entorhinal to hippocampal neurofibrillary changes in both experimental conditions suggests the high vulnerability of the perforant path and hippocampus [ 89 , 90 , 91 , 92 , 93 ]. Therefore, our findings confirm that disruption of the perforant path is one of the key underlying pathophysiological events in the course of AD [ 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%